Learning and leading in the experience age - Jane Cummings (The Beryl Institute, 2017)
A focus on experiences of care helps health systems realize the very transformations they look to achieve. This is because patient experience allows patients, families and carers to define value, enabling healthcare organizations to focus on what matters to them and not simply what is the matter with them. This is what we mean by an ‘experience age’, one in which clear connections are made between the things patients value and the clinical outcomes we look to achieve: where links are drawn between experience, clinical effectiveness, safety and cost in order to provide the very best care for all patients. Central to the experience age is ensuring our health systems: (1) are accountable for the whole patient experience and thus able to act sooner to keep people well and out of hospital, (2) work to establish new relationships with patients, families and carers in which patients, carers and staff work together to establish what matters and how care can be delivered and (3) make stronger connections between patient and staff experience. In committing to these efforts, the global dialogue on patient experience will become even more important, as we recognise that despite differences in design and operation, the challenges our health systems face and the focus on what matters most to patients are shared.